MECHANISMS, EFFICACY, AND SAFETY OF SUZETRIGINE COMPARED WITH OTHER ANALGESICS IN ACUTE PAIN MANAGEMENT - Bartłomiej Rdzanek,; Jakub Żelazo,; Katarzyna Wacławek,; Małgorzata Bacik,; Klaudia Głodowska,; Anna Ciesielka,; Aleksandra Rechcińska,; Kacper Kiereta,; Zuzanna Cichowska,; Laura Chmielowiec,; Witold Czarnik,; Michał Zdybel,; et al. (International Journal of Innovative Technologies in Social Science, 2025)
This review aims to compare the mechanisms of action, efficacy, and safety profiles of suzetrigine with established analgesic classes, including Non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, in the management of acute pain. The objective is to assess whether suzetrigine offers clinical advantages over traditional therapies and to define its potential role in modern multimodal pain strategies.